Cochrane systematic review and meta‐analysis of the impact of psychological treatment on health‐related quality of life in people with epilepsy: an update by the ILAE Psychology Task Force, highlighting methodological changes. Issue 6 (7th January 2022) - Michaelis, Rosa; Tang, Venus; Nevitt, Sarah J.; Wagner, Janelle L.; Modi, Avani C.; LaFrance Jr, W. Curt; Goldstein, Laura H.; Gandy, Milena; Bresnahan, Rebecca; Valente, Kette; Donald, Kirsten A.; Reuber, Markus
Abstract: Clinical interest in using psychological interventions for people with epilepsy (PWE) aiming at decreasing mental health difficulties, improving health‐related quality of life (HRQOL) and seizure‐related outcomes, continues to grow. This article summarizes the 2020 update of the 2017 Cochrane Review and meta‐analysis of psychological interventions for PWE, highlighting the reasons for major methodological modifications such as the recategorization of interventions and expanded risk of bias assessment. A 2020 literature search yielded 36 RCTs ( n =3526) investigating psychological treatments for PWE with a validated HRQOL measure as an outcome. Twenty‐seven trials were skills‐based psychological interventions, whilst nine studies were education‐only interventions. Among skills‐based psychological interventions, 11 studies ( n =643) used the Quality of Life in Epilepsy‐31 (QOLIE‐31) or other QOLIE inventories convertible to QOLIE‐31 as an outcome measure and were pooled for meta‐analysis. Significant mean changes were observed for the QOLIE‐31 total score (mean improvement of 5.23 points; p < 0.001) and in six out of seven subscales (emotional well‐being, energy and fatigue, overall QoL, seizure worry, medication and cognitive functioning). The mean changes in the QOLIE‐31 total score and the overall QoL subscale exceeded the threshold of minimally important change (MIC), indicating clinically meaningful post‐intervention improvement. These results provide moderate evidence that psychological treatments for adults and adolescents with epilepsy enhance HRQOL. In addition to the summary of the Cochrane review, we provide a detailed characterization of the interventions and patient populations of the meta‐analyzed studies.